Management of Spinocerebellar Ataxia through Ayurveda—A Case Report - Punam Sawarkar; Natasha Yadav; Gaurav Sawarkar (Journal of Pharmacy and Bioallied Sciences, 2024)
Spinocerebellar ataxias (SCA) are neurodegenerative disorders marked by progressive cerebellar ataxia, impacting balance, motor coordination, and ocular function due to degeneration. This study evaluated Shodhana Chikitsa and Shaman Chikitsa (purification and symptomatic treatments) for SCA. A 27-year-old man with SCA, showing symptoms like swaying, poor balance, and slurred speech, was referred to the Panchakarma OPD at Ayurveda Hospital, Salod, Wardha. He underwent a comprehensive regimen, including full-body massage with herbal poultices (Patrapottali and Shashtishali Swedana), nasal instillation with medicated oil (Marsha Nasya), and a medicated enema with decoctions and oil, along with oral medications, such as Yogaraja Guggulu, Rasnasaptaka Qwath, Cap Neuron Plus, Agnitundi Vati, and Mahavatavidhwansa Rasa, for two months. Panchtikta Ksheer Vasti (medicated milk enema) was given for eight days. Significant improvements in symptoms and the Scale for Assessment and Rating of Ataxia (SARA) score were observed, suggesting that Ayurvedic treatments may be effective for SCA, warranting further research.